Pemanfaatan Tepung Cangkang Kerang Simping (Amusium pleuronectes) sebagai Pensubstitusi Tepung Terigu dalam Pembuatan Mantau - Neli Muflihah; Yohana Sutiknyawati Kusuma Dewi; Oke Anandika Lestari (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2025)
Bread is a food made from wheat flour and water that is fermented with yeast. In Indonesia, bread has been varied in shape, taste, color, and variety, one of which is mantau. Mantau is rich in nutrients, including protein, carbohydrates and fat, but the calcium content of mantau is still low. Utilization of scallop shell waste in the form of flour as a natural source of calcium in making mantau. This study aimed to obtain the concentration of wheat flour substitution with scallop shell flour needed to produce mantau with the best physicochemical and sensory characteristics. This study used a one-factor Randomized Group Design (RAK), namely scallop shell flour consisting of six levels, namely 0%, 5%, 10%, 15%, 20%, 25% of total flour. The results showed that 5% concentration produced the best sensory characteristics, namely color 3.20 (white), aroma 1.83 (not fishy), texture 3.53 (soft), taste 2.57 (slightly sweet) and overall liking 3.60 (like), and the best physicochemical characteristics with a moisture content value of 31.31% and expandability of 111.41%.